Fungal and Bacterial Pigments: Secondary Metabolites with Wide Applications - Narsing Rao, Manik Prabhu; Xiao, Min; Li, Wen-Jun (Frontiers in Microbiology, 2017)
The demand for natural colors is increasing day by day due to harmful effects of some synthetic dyes. Bacterial and fungal pigments provide a readily available alternative source of naturally derived pigments. In contrast to other natural pigments, they have enormous advantages including rapid growth, easy processing, and independence of weather conditions. Apart from colorant, bacterial and fungal pigments possess many biological properties such as antioxidant, antimicrobial and anticancer activity. This review outlines different types of pigments. It lists some bacterial and fungal pigments and current bacterial and fungal pigment status and challenges. It also focuses on possible fungal and bacterial pigment applications.